How to bridge the couple chasm? - Deylami, Neda; Hassan, Siti Aishah (Faculty of Educational Studies, Universiti Putra Malaysia, 2013)
In this article it is supposed to introduce an affective method in couple therapy called the "Sound Relationship House Theory" (SRH). This theory is integrative approach and as a grounded theory combines existentially-based couple therapy, behavioral couple therapy, cognitive couple therapy, narrative therapy, systematic couple therapy, and psychodynamic couple therapy (J. M. Gottman & Gottman, 2011; J. M. Gottman & Levenson, 1999). The Sound Relationship Theory or Gottman’s theory is supported to advancement of relationships and marriages. This theory explains perception, physiology, and behavior are interactive thermostats in marriage (J. M. Gottman, Coan, Carrere, & Swanson, 1998) and studies marital communication consequences, either negative or positive. Gottman Method Couples Therapy is a structured, goal-oriented, scientifically-based therapy. Intervention strategies are based upon empirical data from Dr. Gottman’s three decades of many longitudinal researches with more than 3,000 couples. According to this method and its strategies every couple can bridge marital chasm and make relationship successful.